2016
DOI: 10.5296/jmr.v8i2.9092
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use and Addiction among Students in Malaysian Public Universities in East Malaysia: Some Empirical Evidence

Abstract: <p>Nowadays, the internet has become an essential part of daily life for most young adult. They mainly use it for <em>education, information searching, entertainment</em>, mail and social interaction purposes. However, extensive use of internet can lead to addiction. This paper presents some preliminary findings on internet use and addiction among Malaysian undergraduate students. A survey questionnaire was used to obtain data from 287 respondents who were business, information technology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Medical students have the opportunity to keep updated with the exponential growth knowledge to become a lifelong learner. The use of the Internet has grown enormously, and students and academicians at universities in Malaysia have started using the Internet for acquiring knowledge, searching information, entertainment, mail, and social interaction 1,2. Rapid expansion and proliferation of the Internet has provided better opportunities for communication, information, and social interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical students have the opportunity to keep updated with the exponential growth knowledge to become a lifelong learner. The use of the Internet has grown enormously, and students and academicians at universities in Malaysia have started using the Internet for acquiring knowledge, searching information, entertainment, mail, and social interaction 1,2. Rapid expansion and proliferation of the Internet has provided better opportunities for communication, information, and social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported that Malaysian university students spend a major portion of their time in accessing the Internet for both academic and extracurricular purposes 1,2,4. One study has reported that Internet usage was very high among university students; therefore, researchers consider it as “pathological Internet use (PIU)” 5.…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals with a stronger sense of loneliness are prone to immerse themselves in the virtual world and use Internet games as a medium to satisfy their innate need for social interactions (Erkoç, Özçakir, & Erkoç, ; Lemmens, Valkenburg, & Peter, ). Currently, most of the studies on loneliness conducted in Malaysia have been mainly focused on Internet and social networking addictions among university students and adolescents (e.g., Cheak, Goh, & Chin, ; Haque et al, ; Teong & Ang, ; Zainudin, Din, & Othman, ). However, studies that have focused on loneliness and IGD are scarce in this context, signifying a substantial literature gap to be filled.…”
mentioning
confidence: 99%
“…1 Addictive use of internet is fast becoming significant problem worldwide and university students are particularly vulnerable for the reason that internet use is an integral part of student life. 2 Literature shows evidence of increasing use of mobile phones and internet among health care professionals. Takeshi Sato compared various studies of internet addiction in student population and reported that the prevalence of internet addiction varies between 8 to 10%.…”
Section: Introductionmentioning
confidence: 99%